THE EFFECT OF THINK, PAIR, SHARE STRATEGY TO IMPROVE STUDENTS SPEAKING ABILITY AT THE SECOND YEAR OF SMAN 1 KOTO KAMPAR HULU - Putri Asilestari (Journal of English Language and Education, 2016)
Think, pair, share strategy is one of speaking strategies that can be used by the teacher. this strategy is a great way to help the students to figure out how to speak english well. it gives students to opportunity to discuss their ideas. it is important because students start to construct their knowledge in discussions and also to find out what they do and do to know. this research was an experimental research. it was conducted at SMA Negeri 1 Koto Kampar hulu which located on kampar regency. the population of this research is the second year students of sma negeri 1 koto kampar hulu. the sample of this research are class xi. 1 as experimental group which consits of 23 students and class xi. 2 consist of 19students as control group. this research focuses of think, pair, share strategy on students speaking ability. The instrument of this research is speaking test in from of speaking performance. the results of these tests were taken as data of this research. the data collection technique that writer used to analyzed data is t-test.